Chemoselective Reduction of Functionalized 5-Nitroisoxazoles: Synthesis of 5-Amino- and 5-[Hydroxy(tetrahydrofuran-2-yl)amino]isoxazoles - Averina, Elena B.; Vasilenko, Dmitry A.; Samoilichenko, Yuri V.; Grishin, Yuri K.; Rybakov, Victor B.; Kuznetsova, Tamara S.; Zefirov, Nikolay S. (Synthesis, 2014)
Reduction by using SnCl2 of easily accessible 5-nitroisoxazoles substituted with an electron-withdrawing group (EWG) has been studied. Whereas the reaction in ethanol yielded 5-aminoisoxazoles, performing the reaction in tetrahydrofuran gave previously unknown 5-[hydroxy(tetrahydrofuran-2-yl)amino]isoxazoles. Both reduction procedures were optimized to afford the corresponding products in good to excellent yields. Some mechanistic details concerning the inclusion of the tetrahydrofuranyl moiety into the reaction product are discussed
Keywords: reduction; chemoselectivity; isoxazoles; radical reaction; tetrahydrofuran